2004
DOI: 10.1111/j.1467-9450.2004.00418.x
|View full text |Cite
|
Sign up to set email alerts
|

Residence arrangements and well‐being: A study of Norwegian adolescents

Abstract: The purpose of this study was to assess any differences in psychosocial problems among adolescents living with both parents, or with their mother or their father. Any benefits of living with a same-sex parent compared to a parent of the opposite sex, was also analysed. A total of 1,686 adolescents aged 14-15 years participated from 29 schools in Hordaland county, including schools in downtown Bergen and more rural areas. The findings revealed significantly more psychosocial problems among the adolescents livin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 30 publications
1
23
0
3
Order By: Relevance
“…This is not an exhaustive list of family background features but rather focuses on the features most frequently linked to academic outcomes. Research indicates that family structure is linked to academic achievement as children and adolescents from intact families (families with two married parents) consistently outperform their peers from single-parent homes on a wide variety of outcomes including grades, standardized achievement test scores, high school completion, and college graduation (Amato and Keith 1991;Amato 2001;Astone and McLanahan 1991;Naevdal and Thuen 2004). Socioeconomic status strongly relates to academic achievement as well, with students of higher socioeconomic levels achieving higher grades, performing better on achievement tests, and persisting with education longer (Gottfried et al 2003;Matsen et al 1999;Teachman 1987).…”
Section: Family Background and Academic Achievementmentioning
confidence: 99%
“…This is not an exhaustive list of family background features but rather focuses on the features most frequently linked to academic outcomes. Research indicates that family structure is linked to academic achievement as children and adolescents from intact families (families with two married parents) consistently outperform their peers from single-parent homes on a wide variety of outcomes including grades, standardized achievement test scores, high school completion, and college graduation (Amato and Keith 1991;Amato 2001;Astone and McLanahan 1991;Naevdal and Thuen 2004). Socioeconomic status strongly relates to academic achievement as well, with students of higher socioeconomic levels achieving higher grades, performing better on achievement tests, and persisting with education longer (Gottfried et al 2003;Matsen et al 1999;Teachman 1987).…”
Section: Family Background and Academic Achievementmentioning
confidence: 99%
“…On the other hand, Breivik and Olweus also observed that the negative effects could, in part, be the result of selection; that is, children with more problems are also to be found in father families more often than other children (see also Spruijt, 2007). Naevdal and Thuen (2004) studied the correlation between well-being and residence arrangements among 1,686 adolescents in Norway. In line with other studies, they concluded that adolescents from intact families score the highest when it comes to well-being, followed by adolescents from mother families.…”
mentioning
confidence: 95%
“…Experiencing parental divorce has been associated with an increased likelihood of exhibiting psychological, behavioral and social problems among children of divorced parents [1-4]. Several prospective and cross-sectional studies among adolescents found that an increase in risk behaviors including cigarette smoking, alcohol intake and substance abuse was associated with experience of parental divorce [5-10].…”
Section: Introductionmentioning
confidence: 99%
“…According to a Norwegian study [4] and three European studies [6, 7, 13], adolescents who lived with both parents drank less [10, 14] and smoked less cigarettes [15] than their peers who lived in other types of families. In investigations of the long-term effect of parental divorce, alcoholconsumption was found to be significantly higher among adults [16] and women [17] who experienced parental divorce during childhood or adolescence than among their counterparts without such experience.…”
Section: Introductionmentioning
confidence: 99%